Partial accelerated degradation test plans for Wiener degradation processes. Issue 1 (2nd January 2019) - Lim, Heonsang; Kim, Yong Soo; Bae, Suk Joo; Sung, Si-Il
Abstract: Securing reliability information on newly developed products is difficult, as only a few samples are available in the development stage. In practice, life tests for new products are conducted under both the normal use condition and accelerated stress conditions. In this study, a two-phase partially accelerated degradation test (PADT) is proposed, which is designed to efficiently obtain product lifetime information in the development stage for new products, when reliability-related information is generally limited and there is limited sample availability. In the first phase, a two-stress-level PADT plan is developed to estimate the parameters of an accelerated degradation model based on the D-optimality criterion. In the second phase, a three-stress-level compromise plan is developed such that the asymptotic variance of maximum likelihood estimate of q -th quantile of the lifetime distribution under the use condition is minimized. Finally, the two-phase systematic test plan is illustrated with a numerical example.